ANDROID CHARACTER GAME BASED ON THE STORY OF THE PROPHET'S FRIENDS AS AN EFFORT TO BUILD STUDENT CHARACTER AT SCHOOL - SULTAN FAKHRUR RASSYI SULTAN; Isro’ullaili Isro’ullaili (Jurnal Kependidikan, 2023)
Character education has always been a controversial topic and an ongoing issue, particularly in Indonesia. The problems related to the rise of criminal incidents such as murder, robbery, fraud, corruption, violence, student brawls, and even cases involving underage perpetrators have persisted without a clear resolution from the government. Many sources point out that these issues stem from the lack of character education in Indonesia, both for children and adults. The deficiency in character education is considered problematic as it can lead to a deterioration of morals, especially among the future generations of the nation. Hence, a solution is needed to aid the government in addressing this issue, leveraging technological advancements and employing methods suitable for all age groups. An innovative solution has emerged in the form of an application called "GAME KARAKTER," which is a story-based Android game application containing the tales of the companions of Prophet Muhammad. The GAME KARAKTER application is designed as a character education tool that not only provides educational content but also integrates gaming and educational elements. The application boasts five key features: the stories of the companions of Prophet Muhammad, interesting facts, gaming, competitions, and evaluations. It is envisioned that GAME KARAKTER can serve as an innovation to assist the government's efforts in promoting character education within the Indonesian nation